2021
DOI: 10.1017/s0008423921000251
|View full text |Cite
|
Sign up to set email alerts
|

The Political Implications of Personality in Canada

Abstract: Few studies have focused on the Canadian context to examine the political impacts of personality. Even though the Canadian Election Study (CES) has measured the Big Five personality traits since 2011, very few studies have taken advantage of this data to assess personality's political role among the Canadian electorate. Using CES data from the three latest elections (2011, 2015 and 2019), we first explore how reliable the measurement of personality is. Except for agreeableness in 2015, the correlations across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 64 publications
3
12
0
Order By: Relevance
“…Finally, extraversion was associated with right-wing self-placement in 2015 and 2019, support for the CPC in 2011 and 2015, and support for LPC in 2015 and 2019. Bergeron and Galipeau's (2021) findings are largely consistent with previous findings relating openness to experience and conscientiousness to ideological placement (Fatke, 2017;Joly et al, 2018).…”
Section: The Canadian Context and Limitations Of Current Researchsupporting
confidence: 91%
See 3 more Smart Citations
“…Finally, extraversion was associated with right-wing self-placement in 2015 and 2019, support for the CPC in 2011 and 2015, and support for LPC in 2015 and 2019. Bergeron and Galipeau's (2021) findings are largely consistent with previous findings relating openness to experience and conscientiousness to ideological placement (Fatke, 2017;Joly et al, 2018).…”
Section: The Canadian Context and Limitations Of Current Researchsupporting
confidence: 91%
“…The largest literature regarding personality and politics examines how personality traits relate to political ideology and partisanship. This research consistently finds that people higher in openness to experience (e.g., curious, artistic, unconventional) are more likely to be on the left of the political spectrum and support liberal parties, while those higher in conscientiousness (e.g., efficient, organized, thorough) tend to be on the right and support conservative parties (Bergeron & Galipeau, 2021; Osborne et al, 2021). The role of personality in explaining political outcomes is not trivial; research has found that personality predicts political ideology with as much strength as demographic correlates like income and education (De Neve, 2015; Gerber et al, 2010).…”
Section: Political Orientationmentioning
confidence: 77%
See 2 more Smart Citations
“…Each main political party in Canada has developed its own customized database, used to generate call sheets and walk sheets for canvassers, often filtering such sheets strategically to target supporters (Munroe and Munroe, 2018; Judge and Pal, 2021; Patten, 2017). Data can be used to target traditional or online advertisements, decide where and who to canvass, track what issue is important to whom, set targets, measure success, quantify individual campaigners’ performance, and make inferences and predictions about electors (for example, data on individuals’ personality traits could be used to infer political ideology [Bergeron and Galipeau, 2021]). The extent to which these features are used varies by party and by campaign (Munroe and Munroe, 2018; Montigny et al, 2019; Giasson et al, 2019; McKelvey and Piebiak, 2019).…”
Section: Current Regulation Of Canadian Political Parties’ Access To ...mentioning
confidence: 99%